The Application of Questioning Skill as a Scientific Approach in Microteaching Practice - Elok Widiyati (Universitas Islam Sultan Agung, 2020)
This study aims to know the pre-service teachers’ skill in teaching by using scientific approach for providing their teaching performance in Internship Program 3. The population of this study was the students of English Education Study Program. Meanwhile, the sample of this study was the students of sixth semester taking Microteaching. This study used qualitative descriptive research. The steps of this study were collecting the data from the sample containing observation and questionnaire. Besides, the data analysis method of this study was data collection and tabulation, they were coding and arranging the data. Hence, the arranged data was interpreted descriptively. The specific goal of this study was to know how the students applied their potential in questioning skill while practicing Microteaching. From the result of question lists in teaching scenario created by the students of Microteaching, it can be concluded that not all of six types of questions were applied by the students. Only four types of questions, they were direct question 34.2%, general and open questions 28.1%, rhetorical question 10.3%, and factual question 27.4%. In other hand, for the types of feedback questions and leading questions were not used at all by the students. For the three main aspects of difficulties faced by the students in questioning aspect skill were the conducive teaching atmosphere 16%, improving students’ activity 14,2%, and the overall spread questions 13.5%.